Recent advances in polysaccharides from Tremella fuciformis: isolation, structures, bioactivities and application - Li, Siyu; Zhao, Ke; Li, Jinjun; Li, Xiaoqiong; Zhao, Hui; Cui, Ruyan; Li, Jianmei; Guo, Jinbin; Bian, Xiangyu (Frontiers in Nutrition, 2025)
Tremella fuciformis, commonly known as snow fungus, is a traditional edible and medicinal fungus widely used in Asian countries for centuries. Its main bioactive constituents, Tremella fuciformis polysaccharides (TFPs), have attracted considerable attention in both food and pharmaceutical industries due to their diverse biological activities. TFPs exhibit a broad spectrum of health-promoting effects, including microbial homeostasis, immuno-modulatory, antioxidant, anti-hyperglycemic, anti-hyperlipidemia, and others. This review summarizes recent advances in the extraction, purification, structural characterization, and pharmacological action of TFPs. The findings suggest that TFPs are promising natural bioactive compounds with potential applications in disease prevention and treatment, and they represent valuable candidates for the development of functional foods and therapeutic agents.